Between a Rock and a Hard Place: a Human Rights Assessment of the Fate of Excluded Asylum-seekers and Criminal Refugees in Australia. (12th August 2022) - Zomignani Barboza, Júlia
Abstract: Migrants fearing harm in their own country may benefit from the protection of refugee law. This protection, however, is not extended to those considered undeserving of it, for example, because they committed atrocities in the past, and may be removed from those who become a threat to the host State's national security. In practice, States need to find solutions for such migrants, who are often failed asylum-seekers or criminal refugees who lost their protection status. In this regard, Australia is infamous for its extensive use of immigration detention, which is frequently applied to such migrants. The country's practices have stirred much academic debate and gave rise to a multitude of legal cases and legislation changes. This contribution provides a human rights assessment of Australia's practices towards failed asylum-seekers and criminal refugees, showing that when faced with such migrants, States may adopt measures that violate their international human rights obligations, such as returning them to harm or placing them in indefinite detention. As States are increasingly adopting similar practices, especially regarding the use of immigration detention, this analysis of the Australian context can inform the assessment of these practices anywhere they may be applied.